Evaluation of high cycle fatigue behaviour of alloy 617M at 973 K: Haigh diagram and associated mechanisms. (May 2019) - Karnati, Abhinav Kumar; Sarkar, Aritra; Nagesha, A.; Parameswaran, P.; Sandhya, R.; Narasaiah, N.
Abstract: Combined influence of mean stress and alternating stress on the high cycle fatigue (HCF) behaviour of Alloy 617 M at 973 K is discussed in the present study. Constant life Haigh diagrams have been generated using different combinations of alternating stress ( σ a ) and mean stress ( σ m ). The alloy exhibited dynamic strain aging (DSA) which is found to strongly influence the cyclic life as well as the fatigue limit. Apart from DSA, presence of annealing twins and carbide precipitation at high temperature during fatigue deformation is also found to positively influence the fatigue life of the alloy. Highlights: Constant life Haigh diagram is generated at 973 K. The alloy exhibited strong dynamic strain aging (DSA). DSA led to allowable stresses higher than YS. DSA delayed the transition in Stage-I to Stage-II crack propagation. Precipitation of Cr23 C6 also contributes to the extensive strengthening of the alloy.